Openness to immigration: a case of Lithuania in an international perspective - Telešienė, Audronė (Sociologija. Mintis ir veiksmas, 2013)
Using the European Social Survey 5th round data (2010/2011) author analyzes openness to immigration. The focus is on the case of Lithuania. Lithuania is exceptional as it has very low but growing rates of immigration. The first question addressed in the paper is the level of Lithuanian population‘s openness to immigration. The openness to immigration of different race and ethnicity than the majority of country’s population was measured. The results show high rates of radical (“allow many immigrants”) and moderate (“allow some”) openness to immigration. Lithuanian population’s openness to immigration is one of the highest in the group of countries that participated in ESS 5th round. The second question asks if perception of threats posed by immigrants can be used as predictor. Logistic regression results show that perception of economic and cultural threats posed by immigrants is a reliable predictor of openness to immigration – low perception of threats leads to openness to immigration.